2014
DOI: 10.1161/hypertensionaha.114.03971
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Vitamin D Receptor in Vascular Endothelial Cells Alters Vascular Function

Abstract: Vitamin D deficiency has been associated with cardiovascular dysfunction. We evaluated the role of the vitamin D receptor (VDR) in vascular endothelial function, a marker of cardiovascular health, at baseline and in the presence of angiotensin II, using an endothelial-specific knockout of the murine VDR gene. In the absence of endothelial VDR, acetylcholine-induced aortic relaxation was significantly impaired (maximal relaxation, endothelial-specific VDR knockout =58% vs. control=73%, p<0.05). This was accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 56 publications
(76 reference statements)
1
108
0
1
Order By: Relevance
“…Mechanistically, the lack of Vdr signaling results in chronically lower bioavailability of the vasodilator nitric oxide (NO) due to reduced expression of NO synthesizing enzyme, and these effects are independent of changes in the renin-angiotensin system (19). In accordance herewith, deletion of the Vdr specifically in endothelial cells results in endothelial dysfunction evidenced by impaired blood vessel relaxation, an effect that was associated with reduced endothelial NO synthase expression (329). Moreover, mice with cardiomyocyte-selective deletion of Vdr also develop cardiac hypertrophy, independent of changes in the renin-angiotensin system and thus indicating a direct in vivo antihypertrophic effect of 1,25(OH) 2 D 3 (78).…”
Section: Mechanisms: In Vitro Data and Mouse Datamentioning
confidence: 65%
“…Mechanistically, the lack of Vdr signaling results in chronically lower bioavailability of the vasodilator nitric oxide (NO) due to reduced expression of NO synthesizing enzyme, and these effects are independent of changes in the renin-angiotensin system (19). In accordance herewith, deletion of the Vdr specifically in endothelial cells results in endothelial dysfunction evidenced by impaired blood vessel relaxation, an effect that was associated with reduced endothelial NO synthase expression (329). Moreover, mice with cardiomyocyte-selective deletion of Vdr also develop cardiac hypertrophy, independent of changes in the renin-angiotensin system and thus indicating a direct in vivo antihypertrophic effect of 1,25(OH) 2 D 3 (78).…”
Section: Mechanisms: In Vitro Data and Mouse Datamentioning
confidence: 65%
“…Vitamin D supplementation has been shown to improve human insulin resistance among patients with glucose intolerance [92,93]. Furthermore, our endothelium-specific VDR knockout mice impaired endothelium-dependent vascular relaxing function, which also contributes to BP elevation [63]. Although further research needs to elucidate the mechanisms by which vitamin D supplementation improves glucose metabolism in type 2 diabetes patients, subsequently lowers BP, the promising preliminary data from these trials are interesting.…”
Section: Effect Of Vitamin D Administration On Bp In Vitamin D-deficimentioning
confidence: 96%
“…BP is regulated by the heart, kidney, vasculature, and sympathetic-CD4+ Tcell system, all of which express VDR. We have made cardiomyocytespecific VDR-/-mice [57], endothelium-specific VDR-null mice [63], and renal collecting duct-specific VDR-/-mice (Chen et al, unpublished data) using aquaporin-2-Cre mice [64], all of which demonstrate normal BP. Increasing evidence has shown that deletion of a single gene in VSMCs can be sufficient to develop HTN [65][66][67][68].…”
Section: Vitamin D Signaling Defect In Vsmcs and Cd+ T Cells Seems Prmentioning
confidence: 99%
“…However, it is unclear whether ELD affected the function of adipose tissue such as the capacity for adipocytokine production. Although endothelial VDR is important for endothelial function (Ni et al 2014), it is not yet known which mechanism is more important in endothelial protection in OVX rats, endothelial VDR activation, or adipocytokine production. There are many reports demonstrated that vitamin D 3 is beneficial for endothelial function.…”
Section: Limitations Of This Studymentioning
confidence: 99%